2021
DOI: 10.1016/j.dsx.2021.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Glycemic control metrics using flash glucose monitoring and hospital complications in patients with COVID-19

Abstract: Background and aims Few studies have reported on the use of continuous glucose monitoring (CGM) during the Covid-19 pandemic. We aimed to examine glycemic control metrics using flash glucose monitoring during insulin treatment and the clinical outcome in hospitalized patients with COVID-19. Methods Prospective, single-center cohort of adult patients diagnosed with type 2 diabetes or hyperglycemia and COVID-19 infection treated with basal bolus insulin regimen. Glycemic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…Sensor insertion was done by a trained nurse, nurse practitioner or healthcare professional in most of the studies [ 35 37 , 38 ▪▪ , 39 , 42 , 43 ]. For the studies using Dexcom G6 system, glucose data was transmitted to Dexcom receivers [ 36 , 42 ], Android phones [ 38 ▪▪ ] or both iPad and iPhones [ 35 ] and were placed close to the patient's room.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sensor insertion was done by a trained nurse, nurse practitioner or healthcare professional in most of the studies [ 35 37 , 38 ▪▪ , 39 , 42 , 43 ]. For the studies using Dexcom G6 system, glucose data was transmitted to Dexcom receivers [ 36 , 42 ], Android phones [ 38 ▪▪ ] or both iPad and iPhones [ 35 ] and were placed close to the patient's room.…”
Section: Methodsmentioning
confidence: 99%
“…Gomez et al used Freestyle Libre CGM to examine the association of glycemic control metrics with clinical outcomes in the ICU and non-ICU setting [ 43 ]. No differences were seen in TIR, TAR, TBR, coefficient of variation or glucose management indicator in patients with or without admission to ICU, ARDS or AKI, or with the composite metric of these complications.…”
Section: Methodsmentioning
confidence: 99%
“…All 16 articles included in the review were original research studies. Included studies represented a wide variety of methodological approaches including: randomized controlled trial (n = 4) [14,15,16,17], retrospective cohort studies (n = 7) [4•, 5•, 6•, 8, 10, 18, 19•, 20], prospective cohort studies (n = 3) [9,21,22], quasi-experimental (n = 1) [23], and qualitative (n = 1) designs [24]. Eight studies included implementation and clinical data collected during the COVID-19 pandemic [4•, 5 [18,26], in the pediatric ICU (PICU) [27], and in a cardiac ICU (n = 1) [28].…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…MARD between Libre CGM and POC AccuChek glucoses was 15.6% with a mean relative difference between Libre CGM and AccuCheck −11.4% [ 49 ]. A second study of Freestyle Libre flash CGM in 60 ICU and non-ICU patients with COVID-19 infection and hyperglycemia or diabetes showed that glycemic monitoring using flash CGM (scanned at least 3 times daily) and a basal bolus insulin regimen was effective in achieving time in range of 72.5% [ 51 ]. Higher time above range > 180 mg/dl was associated with greater rates of a composite of complications [ 51 ].…”
Section: Covid-19 Considerationsmentioning
confidence: 99%
“…A second study of Freestyle Libre flash CGM in 60 ICU and non-ICU patients with COVID-19 infection and hyperglycemia or diabetes showed that glycemic monitoring using flash CGM (scanned at least 3 times daily) and a basal bolus insulin regimen was effective in achieving time in range of 72.5% [ 51 ]. Higher time above range > 180 mg/dl was associated with greater rates of a composite of complications [ 51 ]. This study confirms other studies showing acceptable agreement between the POC glucose values and CGM values and serum glucose and CGM values.…”
Section: Covid-19 Considerationsmentioning
confidence: 99%